Impact of Telemedicine on Healthcare Service System Considering Patients’ Choice - Xiaoli Wang; Zhiyong Zhang; Jun Zhao; Yongqiang Shi (Discrete Dynamics in Nature and Society)
Telemedicine is an effective way to alleviate the congestion of hospitals and improve the utilization of medical resources. In this paper, we develop a stylized queue model to study whether the hospital should adopt telemedicine service and in which form (the gatekeeper system or dual-channel service system) the hospital should provide telemedicine service. Patients’ delay sensitivity and transportation cost are also considered in our model. Our main results follow. First, in most cases, telemedicine service can help to reduce the total cost of the healthcare system, and patients treated online or offline can both benefit from the adoption of telemedicine. Second, the dual-channel healthcare system is more flexible than the traditional outpatient system and the gatekeeper system. There exists an optimal market segmentation of the two channels in the dual-channel healthcare system. Finally, we find that the hospital should implement the telemedicine when the transportation cost is high or patients have a large gap between online and offline waiting sensitivity.